mobbleycam
mobbleycam
04-08-2016
Mathematics
contestada
If f(x)=3x+1 then f(a+h)-f(a)
Respuesta :
princegn
princegn
15-08-2016
f(x) = 3x+1
put x = a+h
f(a+h) = 3(a+h) + 1
f(a+h) = 3a + 3h + 1
put x = a
f(a) = 3a + 1
f(a+h)-f(a) = 3a + 3h + 1 -(3a+1)
f(a+h)-f(a) = 3a +3h + 1 - 3a -1
f(a+h)-f(a) = 3h
Answer Link
VER TODAS LAS RESPUESTAS ( 56+ )
Otras preguntas
I own this company and I have been running this for the last 10 years. Mia, contact the suppliers at once! Dan, this is not immediately about my decision. leade
One half of a melon was shared equally among 3 people. What fraction of the whole melon did each person get? explain
Which pair of angles represent Alternate Exterior Angles? Please helpppp
An equation is shown What values of x make the equation true? x=? x=?
Is this right or wrong ?
Pls help i need help {NO JOKING}
write an algorithm to calculate the sum of integer
A nurse measured a patient heart rate at different times in several days by making a dot plot shown below, describe the shape, center, and spread of the data.
Calculate the volume of the rectangular pyramid below
which one is your favorite (only one) between the second one or the third one the bottom left